The independent and interactive effects of the Big-Five personality dimensions upon dispositional coping and coping effectiveness in sport - Kaiseler, M.; Levy, A.; Nicholls, A. R.; Madigan, D. J. (International Journal of Sport and Exercise Psychology, 2019)
We examined the independent and interactive effects of the Big-Five personality traits on dispositional coping and coping effectiveness among athletes. Participants were 400 athletes (mean age 22.97, s = 7.00) from the UK. The athletes completed measures of personality, dispositional coping, and coping effectiveness. The Big-Five personality traits independently predicted the use of higher order coping dimensions. Extraversion, agreeableness, and openness positively predicted task-oriented coping. Neuroticism positively predicted distraction-oriented coping, whereas agreeableness, extraversion, and conscientiousness were negative predictors. Both extraversion and neuroticism positively predicted disengagement-oriented coping, whereas agreeableness and conscientiousness were negative predictors. Only neuroticism predicted coping effectiveness, which emerged as a negative predictor. Findings also showed a two-way interaction effect for predicting task-oriented coping between neuroticism and openness, and between extraversion and neuroticism. A further two-way interaction effect for predicting distraction-oriented coping was found between agreeableness and conscientiousness. These findings reinforce the need to investigate not only independent, but also interactive effects of personality dimensions upon sport-related dispositional coping.